Ensino da linguagem escrita no contexto da classe hospitalar: um enfoque metalinguístico - Batista, Valéria (2015)
The objective of this research was to analyze the educational care and the teaching of written language in the context of hospital classes, understanding the specificities and possibilities of the pedagogic assistance. It also verified in what extent the written language's teaching practice correspond to a metalinguistic focus. The data collection procedure used semi-structured interviews made with seven teachers of those hospital classes. In the data analysis, we used the content analysis technique, which allowed us to construct thematic categories. It was built three categories, which were: written language, care and the hospital class and family environment. The results showed us that the hospital classes are organized in a different manner than the regular classes; as we analyzed the interviews, we perceived individuals characteristics on the care and environment of hospital classes individual tutoring, multisseriate care with adequate schedules to the hospital routine, what is full of medical procedure, exams, medication, sanitation, feeding, visits. Also, the material is diversified and adapted to the hospitalized children and to the occurring care on different places, such as ICU, insulation room, clinic, Nephrology sector, among others. It was verified on the collected interviews 11 cases of literate children on hospital classes; the investment made so the children could learn to read and write was in order to ensure the achievement of independence in reading and writing. The teachers described 130 offered activities in hospital classes concerning the teaching of written language; they were in large part from the perspective of the metalinguistic focus, to know of: 59,25% characterized by the intentional thinking of the phonological awareness (77), 13,85% of the textual awareness (18), 11,55% of the pragmatic awareness (15), 6,90% of the semantic awareness (9), 6,90% of the syntactic awareness (9) and 1,55% of the morphological awareness (2). We concluded that the offered education of the hospital class context has potential to foster the re-insertion of children into the regular school. Therefore, it contributes to minimize the scholar drift, especially if the teacher focuses on the written language education through the metalinguistic focus. We believe on the benefits presented by the Cognitive Psychology of Reading researches relating to the work of linking metalinguistic activities with the learning of written language and we indicate that such activities are given on entertaining and interesting situations by using games and educational software and thus turning the educative situation more attractive and interesting to the hospitalized children and teenagers so it all contributes to an effective teaching of written language